Proceedings of the Twenty-Second IEEE/ACM International Conference on Automated Software Engineering 2007
DOI: 10.1145/1321631.1321676
|View full text |Cite
|
Sign up to set email alerts
|

The business case for automated software engineering

Abstract: Adoption of advanced automated SE (ASE) tools would be more favored if a business case could be made that these tools are more valuable than alternate methods. In theory, software prediction models can be used to make that case. In practice, this is complicated by the "local tuning" problem. Normally, predictors for software effort and defects and threat use local data to tune their predictions. Such local tuning data is often unavailable.This paper shows that assessing the relative merits of different SE meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 23 publications
0
43
0
Order By: Relevance
“…year at ICSP'08 and elsewhere [6][7][8]) we showed that this methods can yield estimates close to those seem using traditional methods, without requiring a time consuming data collection exercise.…”
Section: Fourth Reusementioning
confidence: 57%
“…year at ICSP'08 and elsewhere [6][7][8]) we showed that this methods can yield estimates close to those seem using traditional methods, without requiring a time consuming data collection exercise.…”
Section: Fourth Reusementioning
confidence: 57%
“…We have conducted experiments with other approaches that allow intermediate values. On comparison with the simulated annealing method used in a prior publications [16], we found that seesawing between {Low, High} values was adequate for our purposes.…”
Section: Finding Alternatives To Drastic Changementioning
confidence: 86%
“…This is due to data not being collected or the business sensitivity associated with the data as well as differences in how the metrics are defined, collected and archived. For example, after two years we were only able to add 7 records to a NASA-wide software cost metrics repository [16]. Having failed to generate precise tunings, we developed SEESAW to discover what stable conclusions we could find within the space of possible tunings.…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations